2006
DOI: 10.1021/ci0600511
|View full text |Cite
|
Sign up to set email alerts
|

A Steroids QSAR Approach Based on Approximate Similarity Measurements

Abstract: A new QSAR method based on approximate similarity measurements is described in this paper. Approximate similarity is calculated using both the classical similarity based on the graph isomorphism and a distance computation between nonisomorphic subgraphs. The latter is carried out through a parametric function where different topological invariants can be considered. After optimizing the contribution of nonisomorphic distance to the new graph similarity, predictive models built with approximate similarity matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The one-complement D of the Tanimoto/Jaccard coefficient, where D=1J, has been proven to be a real metric, satisfying all the known properties of distance measures [35]. In comparison to vector space-based methods, there is limited research reported in the literature exploring the quantitative relationship between computed molecular similarity and activity in QSAR/QSPR modeling [7,16,19,36,37,38,39,40,41,42,43,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…The one-complement D of the Tanimoto/Jaccard coefficient, where D=1J, has been proven to be a real metric, satisfying all the known properties of distance measures [35]. In comparison to vector space-based methods, there is limited research reported in the literature exploring the quantitative relationship between computed molecular similarity and activity in QSAR/QSPR modeling [7,16,19,36,37,38,39,40,41,42,43,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Urbano-Cuadrado et al obtained the relative distances between molecules of the data set for the calculus of approximate similarity measurements according to the nonisomorphic fragments obtained from the extraction of the maximum common subgraph (MCS) of the data set and combined similarity measurements and approximated similarity to generate data models which take into account, using relative measurements, the nonisomorphic fragments that determine the variability in the property that is being studied …”
Section: Introductionmentioning
confidence: 99%
“…The selection process does not involve a modification in the structure of the fingerprints. 16 Urbano-Cuadrado et al 17 obtained the relative distances between molecules of the data set for the calculus of approximate similarity measurements according to the nonisomorphic fragments obtained from the extraction of the maximum common subgraph (MCS) of the data set and combined similarity measurements and approximated similarity to generate data models which take into account, using relative measurements, the nonisomorphic fragments that determine the variability in the property that is being studied. 11 McLellan et al 18 studied the rank order entropy for the validation of QSAR models, varying the training and test data sets and observing the data strength.…”
Section: Introductionmentioning
confidence: 99%
“…Models based on topological descriptors or graph isomorphism (computed using 2D structures representing chemical graphs) are often considered as quick methods when they are compared with other 3D approaches. The latter requires the searching and optimization of 3D conformations, which are complex and time-consuming processes when bulky and flexible molecules compose the data set.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding isomorphism calculation, we have recently developed a new similarity concept, the approximate similarity (AS) measurement, based on computing similarities and distances of common and noncommon subgraphs, respectively.…”
Section: Introductionmentioning
confidence: 99%